2017
DOI: 10.2147/tcrm.s137103
|View full text |Cite
|
Sign up to set email alerts
|

Onset of chronic myeloid leukemia with complex karyotype in a pregnant patient: case report and revision of literature

Abstract: Approximately 10%–12% of patients in chronic-phase chronic myeloid leukemia (CP-CML) have additional chromosomal aberrations at diagnosis; moreover, CML occurs in up to 10% of pregnancy-associated leukemias, with an annual incidence of 1 per 100,000 pregnancies. In this report we describe the case of a 36-year-old female with CP-CML diagnosed in the 18th week of pregnancy and with a new complex variant translocation t(4;9;22;21)(q24;q34;q11;q22) and an additional chromosomal aberration t(1;20)(p36;p11). In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…This patient was never compliant with the medicine. To the best of our knowledge, few case reports have been published internationally reporting chronic myeloid leukemia with complex karyotype and molecular remission [ 25 ]. One of our patients diagnosed as aplastic anemia on bone marrow biopsy had complex karyotype and died due to septic shock early during the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…This patient was never compliant with the medicine. To the best of our knowledge, few case reports have been published internationally reporting chronic myeloid leukemia with complex karyotype and molecular remission [ 25 ]. One of our patients diagnosed as aplastic anemia on bone marrow biopsy had complex karyotype and died due to septic shock early during the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with Ph− cells, ACA found could be a reciprocal translocation t (6; 9) (p21; q34.1), a chromosomal marker (+ mar), a trisomy 8 and others. On the other hand, the absence of the Ph chromosome and the presence of − 7 (monosomy 7) contribute to the evolution towards a myelodysplastic syndrome (MDS) or acute myeloid leukemia (AML) [12,19].…”
Section: Cytogenetics Of Chronic Myeloid Leukemiamentioning
confidence: 99%
“…Most of the patients in blastic phase have a myeloid phenotype while 25% show a pre B lymphoblastic phenotype [1]. It has been reported that around 10% to 12% of patients with CML in chronic phase have ACAs at the time of diagnosis [9].…”
Section: Introductionmentioning
confidence: 99%